Analyzing the Efficiency and Profitability Determinants: Evidence from Chinese Banks, 2006-2012 - WANG, Chuanyun (2014)
This study examines the efficiency and determinants of bank profitability by using data from 37 banks in Beijing, Shanghai, Guangzhou and Shenzhen in China over the period of 2006-2012. Distinct from previous studies, we conduct a two-stage analysis. In the first stage of the paper, X-efficiency is estimated using the stochastic frontier approach (SFA). The results suggest that in the highly concentrated Chinese banking market, the managerial efficiency of the banks has improved year by year with average efficiency level of about 91% for the overall period. In the second stage for estimation of determinants of bank profitability employing system GMM regressors, we find evidence that larger, well capitalized banks with lower credit risks and more liquidity level tend to outperform smaller, less capitalized rivals with higher credit risks and less liquid assets. Besides that, macroeconomic factors such as GDP growth rate, growth of money supply and market concentration are found not affecting bank profitability significantly. Moreover, a series of regulatory adjustments by Chinese government are regarded as valid and efficient instruments to bring back Chinese economies from global financial crisis.